A Seat at the Table: An Examination of Hospital Governing Board Diversity, 2011–2021. Issue 2 (24th March 2023) - Silvera, Geoffrey A.; Erwin, Cathleen O.; Garman, Andrew N.
Abstract : Goal: Board diversity is increasingly important for hospitals and healthcare systems, with national attention focused on eliminating health disparities and improving health equity. Yet, it remains a challenge despite concerted efforts by leading professional associations (e.g., American College of Healthcare Executives) to galvanize their constituents around the importance of the issue. Methods: This study used survey data from The Governance Institute to explore the ethnoracial and gender diversity of hospital boards spanning 2011 through 2021. Principal Findings: The results showed modest gains in the mean number of female board members, although a small proportion of hospital boards still have no female representation. There was little change in the number of boards with ethnic minority representation until an uptick in 2021, likely in direct response to high-profile racial incidents and protests. Practical Applications: Intentional and sustained efforts are necessary to increase diversity and create a culture of inclusion that fosters meaningful engagement of diverse board members.